Visco-elastic parasitic folding: Influences on the resulting porosity distribution. (January 2020) - Liu, Xiaolong; Eckert, Andreas; Connolly, Peter; Thornton, Dean
Abstract: Parasitic folds represent a common structure of multi-scale multilayer folds and the resulting asymmetric S- or Z-shapes and symmetric M-shapes represent a complex strain distribution. How the strain evolution affects the resulting porosity remains unclear. In this study, a 2-D plane strain finite element modeling approach is used to simulate multi-scale, multilayer, viscoelastic buckle folds under in-situ stress and pore pressure conditions. A variety of material and model parameters (including the elastic modulus contrast, number of layers, viscosity contrast, strain rate and layer thickness ratio) are considered and their influence on the shape of parasitic folds and on the resulting porosity distribution is analyzed. This study demonstrates that the shapes of the parasitic folds depend on the buckling of both the large- and small-scale folds and are influenced by the various parameters. The numerical modeling results show a large variability in porosity changes as a result of the complex distribution of the volumetric strain during the multi-scale, multi-layer buckling process. Three regions, including the hinge and limb of the less competent layer in the M-shaped folds and the limb of the less competent layer in the Z-shaped folds, feature significant porosity changes, which vary from double the initial magnitude to almost zero. In addition, the numerical simulations provide a general understanding of the influence of the various model parameters on the resulting porosity distribution. Through the applied volumetric strain-porosity-permeability coupling, the resulting fluid flow regimes in multi-scale, multilayer buckling systems include localized pervasive and focused regimes.